Structural health monitoring with piezoelectric wafer active sensors - Giurgiutiu, Victor (Elsevier/Academic Press, 2014)
Structural Health Monitoring with Piezoelectric Wafer Active Sensors, 2nd Edition provides an authoritative theoretical and experimental guide to this fast-paced, interdisciplinary area with exciting applications across a range of industries. The book begins with a detailed yet digestible consolidation of the fundamental theory relating to structural health monitoring (SHM). Coverage of fracture and failure basics, relevant piezoelectric material properties, vibration modes in different structures and different wave types provide all the background needed to understand SHM and apply.
Keywords: Structural analysis (Engineering); Automatic data collection systems.; Piezoelectric devices.; Piezoelectric transducers.; elektronické knihy; electronic books